Fully biobased robust biocomposites of PLA with assisted nucleation by monodispersed stereocomplexed polylactide particles - BiBi, Gulnaz; Jung, Yongmee; Lim, Jongchoo; Kim, Soo Hyun (ROYAL SOC CHEMISTRY, 2016)
Fully biodegradable biocomposites are a desirable choice among the synthetic plastics due to their increasing adverse ecological issues. Stereocomplexed polylactide submicronparticles (s-PLA SP), which provide dense nucleating sites to PLLA in the crystallization process, were used to prepare homogenous PLLA biocomposites to enhance the thermal and mechanical properties of PLLA. Herein, we report the synthesis of monodispersed s-PLA SP and preparation of biocomposites of PLLA incorporating s-PLA SP. The synthetic system for s-PLA SP is comprised of two steps. The first step involves solvating PLLA and PDLA in respective reactors. The second step is the stereocomplexation of the dissolved polymer in the mixing reactor. The polymer solvation conditions greatly affect the s-PLA particle size and distribution. Therefore, we studied the variation of s-PLA particle size and polydispersity index (PDI) due to the effect of the polymer solvation parameters, such as homopolymer concentration, solvation time, temperature, pressure and molecular weight, as the first step. The optimum conditions established were 50 degrees C, 300 b, with 5% homopolymer solvation for 12 h. In the second step, s-PLA SP formation was carried out at the previously established reaction conditions of 70 degrees C, 250 b for 2 h. The PLA homopolymers (M-n similar to 57 kg mol(-1)) produced s-PLA SP smaller than 963 nm with a PDI of 0.12, as analyzed by DLS and SEM at the optimum reaction conditions. We cast completely biobased homocomposites (BC) for high performance by homogeneously dispersing s-PLA SP in the high molecular weight PLLA matrix (M-n similar to 200 kg mol(-1)) in chloroform, followed by annealing. The solution casting DSC results show the enhanced crystallization of PLLA for various compositions of BC ranging from 0.5% to 5%. An increase in the concentration of s-PLA SP increases the thermal and mechanical properties of the PLA BC. Effective nucleation with decreased spherulite size was noticed for the 5% BC with 963 nm s-PLA SP incorporated into the casting solution, as inferred by SEM analysis. The tensile strength and Young's modulus increased from 29 MPa to 73 MPa and 1.3 GPa to 3.2 GPa, respectively, whereas the X-cc increased from 20% to 35% and T-cc increased from 98 degrees C to 113 degrees C with the 5% composition involving 963 nm s-PLA SP.
Keywords: CRYSTALLIZATION BEHAVIOR; MECHANICAL-PROPERTIES; POLY(L-LACTIC ACID); BLENDS; NANOSTRUCTURES; MORPHOLOGY; AGENT